Research on the Training Strategy of Aerobic Physical Education Talents under the Background of Artificial Intelligence Era - Xiaojing Liu; Hong Wang (Applied Bionics and Biomechanics)
Aerobic is loved by the public, especially the young people, through the combination of the art and power of dance. With people’s attention to health, the demand for aerobic professionals is increasing. As an important training base for aerobic professionals, the level and teaching ability of aerobic professionals have a great influence on students. The gradual maturity and rapid popularization of artificial intelligence bring many opportunities and challenges to the teaching of physical education in colleges and universities. Only by seizing the opportunities and facing the challenges, excavating their own existing problems, and transforming with the help of artificial intelligence can we adapt to the development trend of educational modernization in China. In order to increase the standardization and standardization of aerobics and provide executable standards for aerobic learning, performance, and adjudication, through the research on the training strategy of aerobic sports talents under the background of artificial intelligence era, capture aerobic performance actions with artificial intelligence awareness, standardize and standardize aerobics, and discuss the teaching effect of school intelligent aerobics, it is found that this study not only has important physical education teaching value but also relates to the application prospect of artificial intelligence technology in aerobic physical education talent training strategy.